2005
DOI: 10.1159/000087748
|View full text |Cite
|
Sign up to set email alerts
|

The Basis of Gender Assignment in Disorders of Somatosexual Differentiation

Abstract: Sex assignment of patients with disorders of somatosexual differentiation is a controversial topic. The aim is to enable the patient to develop a stable gender identity during childhood, adolescence and adulthood. Enormous advances have recently been made in our knowledge of the molecular mechanisms of sexual differentiation and it is understood that long-term outcome may depend on the underlying diagnosis. There is increasing evidence that genital development is dependent on the action of androgenic steroids;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
15

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 19 publications
0
37
0
15
Order By: Relevance
“…92,93 These decisions must be based on the correct diagnosis, which will facilitate prediction of development during puberty and adulthood in affected individuals. 94 Whether virilization will increase at puberty or following androgen therapy in a neonate with ambiguous genitalia is a crucial question. Kohler et al 70 suggest a testosterone treatment trial in all patients with PAIS in order to evaluate the virilizing capacity of the newborn external genitalia before sex assignment.…”
Section: Management Of Ais Patientsmentioning
confidence: 99%
“…92,93 These decisions must be based on the correct diagnosis, which will facilitate prediction of development during puberty and adulthood in affected individuals. 94 Whether virilization will increase at puberty or following androgen therapy in a neonate with ambiguous genitalia is a crucial question. Kohler et al 70 suggest a testosterone treatment trial in all patients with PAIS in order to evaluate the virilizing capacity of the newborn external genitalia before sex assignment.…”
Section: Management Of Ais Patientsmentioning
confidence: 99%
“…Gynecomastia does not usually occur, but has been reported in some patients [161]. A recent literature review reported that female-to-male gender role change occurs frequently (39-64 %) but not invariably, usually in late adolescence or early adulthood [77,[159][160][161][162]. As in 5-alpha-reductase deficiency, in 17-beta-HSD-3 deficiency, there is not to date a clear relationship between the severity of the enzymatic defect and gender identity and why changes in gender role occur in some patients but not in others [77,[162][163][164][165][166][167].…”
Section: -Beta-hsd-3 Deficiencymentioning
confidence: 99%
“…A recent literature review reported that female-to-male gender role change occurs frequently (39-64 %) but not invariably, usually in late adolescence or early adulthood [77,[159][160][161][162]. As in 5-alpha-reductase deficiency, in 17-beta-HSD-3 deficiency, there is not to date a clear relationship between the severity of the enzymatic defect and gender identity and why changes in gender role occur in some patients but not in others [77,[162][163][164][165][166][167]. Moreover, it has been suggested that unidentified pre-and postnatal factors, a better knowledge of the natural history of the disorder in some areas, and sociocultural issues may participate, all together, in influencing gender identity and role [77,161,163].…”
Section: -Beta-hsd-3 Deficiencymentioning
confidence: 99%
“…Now most experts would agree that biological characteristics (such as chromosomal pattern, nature of the gonad, and so on) are not sufficient to provide reliable indicators for determining a person's 'true' sex status as a man or woman. [3][4][5][6][7] Though relevant, they presently do not fully govern the decision to assign a particular sex to a newborn with ambiguous genitalia. A widely adopted policy is to arrive at a prognosis on the 'optimal sex' for the newborn, the elements of which are an overall sex-appropriate appearance with stable gender identity, good sexual function (preferably combined with reproductive function if attainable), minimal medical/surgical procedures, and a reasonably fulfilling life hampered as little as possible by the condition.…”
Section: Intersexed Statesmentioning
confidence: 99%
“…A widely adopted policy is to arrive at a prognosis on the 'optimal sex' for the newborn, the elements of which are an overall sex-appropriate appearance with stable gender identity, good sexual function (preferably combined with reproductive function if attainable), minimal medical/surgical procedures, and a reasonably fulfilling life hampered as little as possible by the condition. [4][5][6][7][8] The extensive experience with this policy has vindicated the view that self-awareness of being man or woman is not exclusively dependant on biological determinants of sex alone (chromosomes, gonads, genitalia and hormones). While these are not irrelevant, other factors, still largely unidentified, also play a significant role.…”
Section: Intersexed Statesmentioning
confidence: 99%